2017
DOI: 10.1117/1.jmi.4.2.027001
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced axial and lateral resolution using stabilized pulses

Abstract: Ultrasound B-scan imaging systems operate under some well-known resolution limits. To improve resolution, the concept of stable pulses, having bounded inverse filters, was previously utilized for the lateral deconvolution. This framework has been extended to the axial direction, enabling a two-dimensional deconvolution. The modeling of the two-way response in the axial direction is discussed, and the deconvolution is performed in the in-phase quadrature data domain. Stable inverse filters are generated and app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Most methods assume an identical, independent noise. In the works of Parker and colleagues, [25][26][27] the emphasis was mostly on the resolution enhancement; however, the CNR change was not reported. As mentioned in these papers, the drawback of this is the increased noise.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Most methods assume an identical, independent noise. In the works of Parker and colleagues, [25][26][27] the emphasis was mostly on the resolution enhancement; however, the CNR change was not reported. As mentioned in these papers, the drawback of this is the increased noise.…”
Section: Discussionmentioning
confidence: 99%
“…In y , there is also the effect of speckle and electronic noise. Due to the nature of the speckle, the noise formation in medical ultrasound is better modeled with a multiplicative term 11,27,44 ; however, for B-mode ultrasound images, it has been shown that the linear and additive model in Equation (2) is appropriate since B-mode images are subjected to the log compression operation 33,35,36,44 :…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A large proportion of current ultrasonic imaging systems utilize phased and linear array emitters combined with beamforming and signal processing techniques. Various metrics are used in literature to quantify the resolution of a system including full width at half maximum (FWHM) and minimum separation detectable (MSD) between adjacent objects [5][6][7][8] . For single element emitters, the FWHM for a focused Gaussian beam is defined as FWHM 1:06λF a ;where F is the focal length, λ is the wavelength, and a is the aperture 9 .…”
mentioning
confidence: 99%